(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The article presents the results of a study of the process of cleaning cotton from weeds in sections of screw conveyors. Screw conveyors have a special role in the technological process of cotton gins, they are used for the transport and distribution of cotton technological machines. Based on the analysis of the operation of screw conveyors, a device was developed for cleaning raw cotton from small weeds during transportation. A theoretical description of the process of cleaning raw cotton from impurities is proposed, according to the model proposed in the literature by A.G. Sevostyanov. An assessment of the influence of the number of sections and pins on the cleaning effect of the conveyor is given.